Influence of psychosocial factors and parent–student relationships on the academic engagement of TCM students: a structural equation modeling and multi-criteria decision-making framework - Liang Shaoshuai; Peng Qian; Zhang Yiwen; Xu Meiru (Frontiers in Psychology)
BackgroundStudents with high IQs often underperform in practice-oriented fields like Traditional Chinese Medicine (TCM) because they lack the emotional regulation, stress management, and interpersonal skills needed to realize their academic potential. Recent research underscores the critical role of psychosocial competencies—emotional quotient (EQ), adversity quotient (AQ), and psychological resilience (PR)—in bridging cognitive potential and real-world academic success. Furthermore, the interplay between EQ, AQ, PR, and parent-student relationships, an underexplored dimension in higher education, may serve as a stabilizing force against academic stressors.MethodsThe study involved 428 Traditional Chinese Medicine (TCM) students who underwent comprehensive evaluations to assess EQ, AQ, PR, parent-student relationships, and academic engagement. Structural equation modeling (SEM) via SmartPLS analyzed causal pathways, while the VIKOR-AHP method addressed MCDM by (1) weighting criteria via AHP and (2) ranking interventions via VIKOR’s compromise-ranking, ensuring practical solutions amid real-world constraints.ResultsThis study examined the impact of EQ, AQ, PR, and parent-student relationships on the academic engagement of TCM students. The results indicated that engagement was directly influenced by EQ, while it was indirectly enhanced through improved PR and AQ. During academic challenges, parental-student relationships emerged as a significant moderator. EQ and AQ were identified as the most critical factors in promoting academic engagement. To ensure robustness, a sensitivity analysis was performed to assess how variations in experts’ weights influenced the outcomes, thereby validating the stability and reliability of the results under uncertainty.ImplicationsThis study, grounded in Csikszentmihalyi’s flow theory, proposes specific strategies to enhance academic engagement. While students often possess adequate cognitive abilities, they require improved emotional regulation and stress management skills to convert potential into achievement. Educational institutions should integrate emotional quotient training with traditional cognitive curricula, alongside resilience-building programs and efforts to foster parent-student collaboration. These non-cognitive approaches not only improve academic performance but also promote personal adaptability. The findings advocate for comprehensive educational frameworks that combine cognitive and psychosocial development to optimize student engagement.